Toxoplasmosis Recent Advances - Djurković Djaković, Olgica (IntechOpen, 2012)
A ubiquitous organism able to infect all mammals and birds, which has been estimated to infect one third of the global human population, Toxoplasma gondii is the most successful parasite on Earth, and toxoplasmosis a major zoonotic disease. A current approach to this zoonosis is the "one health" concept, based on the understanding that a disease occurring between animals and man in a specific environment can only be dealt with at the interface of all "players" involved. This book, composed of a series of articles which integrate human and animal data on toxoplasmosis, by authors from all over the world, offers its readers a view on the current research interests and achievements.